Voltage sag and the sensitive load - Ismail, Daut; Che Mat Hadzer, Mahmud; Surya, Hardi; Risnidar Chan, Bahaudin; Saedah, Siraj; Nor Haidar, Hashim (Universiti Malaysia Sarawak (UNIMAS), 2008)
Organized by Universiti Malaysia Sarawak (UNIMAS), 27th - 28th December 2007 at Kuching, Sarawak, Malaysia.